A Flexible, Stretchable and Shape‐Adaptive Approach for Versatile Energy Conversion and Self‐Powered Biomedical Monitoring. (15th May 2015) - Yang, Po‐Kang; Lin, Long; Yi, Fang; Li, Xiuhan; Pradel, Ken C.; Zi, Yunlong; Wu, Chih‐I; He, Jr‐Hau; Zhang, Yue; Wang, Zhong Lin
<x xml:space="preserve">Abstract</x> A flexible triboelectric nanogenerator (FTENG) based on wavy‐structured Kapton film and a serpentine electrode on stretchable substrates is presented. The as‐fabricated FTENG is capable of harvesting ambient mechanical energy via both compressive and stretching modes. Moreover, the FTENG can be a bendable power source to work on curved surfaces; it can also be adaptively attached onto human skin for monitoring gentle body motions.